2020
DOI: 10.3390/healthcare8030198
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Family Physicians in a Pandemic: A Blueprint

Abstract: Pandemics are a significant stress test for a country’s economic, political and health systems. An effective pandemic response demands a multi-pronged and multi-layered approach, comprising surveillance, containment, border control, as well as various social and community measures. In the wake of the novel coronavirus disease 2019 (COVID-19) pandemic, which has now infected more than 7 million people worldwide, strict quarantine measures are a commonplace, and a third of the world’s population have now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
0
28
0
2
Order By: Relevance
“…Since the beginning of the pandemic, clinical activities have been remotely reorganized to reduce impact on the National Health System. A working model in telemedicine has been developed [61] and could be especially helpful for children with higher susceptibility to sociodemographic and environmental factors and previous emotional and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the pandemic, clinical activities have been remotely reorganized to reduce impact on the National Health System. A working model in telemedicine has been developed [61] and could be especially helpful for children with higher susceptibility to sociodemographic and environmental factors and previous emotional and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals should take the opportunity to provide resources for psychological support and interventions for those who present with poor health status. Further, health authorities need to provide accurate health information during the pandemic to reduce the spread of misinformation [ 26 , 27 ]. Third, Chinese international students who are abroad may face unfair treatment and be discriminated against in some countries, being viewed as possible COVID-19 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…For the anxiety subscale, 132 (50.6%) were considered to have a normal score (score: 0-6); 30 (11.5%) were considered to suffer from mild anxiety (score: 7-9); 69 (26.4%) were considered to suffer from moderate anxiety (score: 10-14); and 30 (11.5%) were considered to suffer from severe or extremely severe anxiety (score: 15-42). For the stress subscale, 164 (62.8%) were considered to have a normal score (score: 0-10); 79 (30.3%) were considered to suffer from mild stress (score: 11-18); 18 (6.9%) were considered to suffer from moderate stress (score: 19-26); and none of them were considered to suffer from severe or extremely severe stress (score: [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Though international students in the U.S. also showed lower scores on the DASS stress subscale (8.72 ± 5.9, p = 0.559, B = −0.04, 95% CI: −1.98 to −0.07), there was no statistically significant difference when compared to the international students in China (Tables 1 and 2). We found that the percentage of DASS depression, DASS anxiety, and DASS stress subscale scores above their cutoff point among international students in China were higher than those among international students in the U.S. (53.6% vs. 32.2%, 53.6% vs. 53.1%, and 40.8% vs. 33.1%, respectively; Figure 1a), and the percentage of PTSD PCL-C scores above 38 among international students in China was larger than that among international students in the U.S. (41.6% vs. 40.0%; Figure 1b).…”
Section: Demographic Characteristics and Their Association With Psychmentioning
confidence: 99%
“…In Malaysia, the role of primary care physicians, who comprise general practitioners (GP) and family medicine specialists (FMS), as the gatekeepers of health, is a general understatement. The primary care physician manages the patient in the context of their family and community while recognizing the broader determinants of health with links to public health (11)(12)(13). At the same time, the physician examines the full spectrum of disease, intervenes early to maintain wellness, and delays the onset of sickness (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%